RP-HPLC method development and validation of Abacavir, Lamivudine and Zidovudine in combined pharmaceutical dosage by analytical QbD - Divyesh Vanparia; Ronak R. Dedania; Zarna R. Dedania (Discover Chemistry)
Abstract An accurate, precise, robust, and green RP-HPLC method was developed for assessment of three antiviral medications, namely Abacavir (ABA), Lamivudine (LAMI), and Zidovudine (ZIDO) in combined pharmaceutical dosage form by Analytical Quality by Design (AQbD) approach. The Box-Behnken design describes the interrelationship mobile phase, pH and flowrate to the resolution of drugs. The method was optimized using Design Expert® (Version 11.0), i.e. Inertsil ODS, C18 (250 mm × 4.6 mm × 5 µm) column; mobile phase methanol: acetonitrile: potassium dihydrogen phosphate (pH 3.5), 65:20:15% v/v/v at a flow rate of 1.0 mL/min at 280 nm detection wavelength. The retention times for ABA, LAMI, and ZIDO were found to be 4.12 min, 6.71 min and 9.25 min respectively. The linearity was found 10–60 µg/mL ZIDO, 5–30 µg/mL LAMI, and 10–60 µg/mL ABA. The greenness score indicates Eco friendliness of developed method with minimal amount of toxic reagents used and waste generation.